PATH-40. TARGETED NEXT GENERATION SEQUENCING (NGS) OF YOUNG ADULTS WITH ISOCITRATE-DEHYDROGENASE WILD-TYPE GLIOBLASTOMA (IDH-WT GBM) REVEALS NEGATIVE PROGNOSTIC IMPACT OF EPIDERMAL GROWTH FACTOR RECEPTOR AMPLIFICATION (EGFRAMP). (5th November 2018) - Hoffman, Daniel; Abdullah, Kalil; Binder, Zev; O'Rourke, Donald; Desai, Arati; Morrissette, Jennifer; Brem, Steven; Bagley, Stephen
Abstract: BACKGROUND: Young adults with IDH-WT GBM represent a rare, understudied population compared to pediatric, IDH-mutant, or typical (elderly) GBM. We aimed to explore clinically detected genomic alterations in this population and their prognostic impact. METHODS: We identified patients ages 21 45 with newly diagnosed, previously untreated IDH-WT GBM whose tumors underwent NGS at our institution. Patients with hereditary cancer syndromes were excluded. The NGS panel detects pathogenic variants by targeted exome sequencing of 47 (2014–2016) or 153 (2016-present) genes. Clinical characteristics and overall survival (OS) were collected. These data were also collected from a contemporaneous cohort of older (>=65) patients with newly diagnosed, IDH-WT GBM. RESULTS: 28 young and 30 older patients were included. In young patients, 12 (43%) had an EGFR alteration [2 (7%) EGFR mutation, 7 (25%) EGFR amplification (EGFRamp), and 3 (13%) both EGFRamp and EGFRvIII]. Other mutations detected in 2 young patients were TP53 in 7 (25%), BRAF (V600E) in 3 (11%), RB1 in 3 (11%), PTEN in 2 (7%), SETD2 in 2 (7%), and DNMT3A in 2 (7%). Differences detected in older vs. younger patients were more frequent PTEN mutations (27% vs. 7%, p=0.049) and MGMT methylation (50% vs. 25%, p =0.06). In young patients, median OS was 19.5 months (95% CI 15.9–24.4), and EGFRamp was associated with inferior median OS (16.3 vs. 23.5 months, p=0.047). There was no difference in OS by EGFRamp in older patients. CONCLUSIONS: EGFRamp was associated with inferior OS in this contemporary cohort of young adults with IDH-WT GBM, whereas no association was detected in older patients. This suggests a potential role for targeting EGFR specifically in this population. In addition, consistent with prior studies, we found that MGMT methylation is less common in young patients with IDH-WT GBM, highlighting the need for alternatives to temozolomide.